Standard operation procedures and protocols used in forage breeding programme using remote and proximal sensing tools - Camelo Munevar, Rodrigo Andrés (CGIAR Initiative on Accelerated Breeding, 2023)
This methodology is applied to the planning and execution of image processing of the Tropical Forage genetic breeding program at CIAT, Cali, Colombia. This methodology allows you to work with RGB panoramic images instead of multispectral orthomosaics efficiently, reducing the image storage space, equipment and software required and optimizing the time and number of operators assigned to this activity.